Real Assets and Capital Structure - Campello, Murillo; Giambona, Erasmo (Journal of Financial and Quantitative Analysis, 2013)
Abstract We characterize the relation between asset structure and capital structure by exploiting variation in the salability of corporate assets. To establish this link, we distinguish across different assets in firms’ balance sheets (machinery, land, and buildings) and use an instrumental approach that incorporates market conditions for those assets. We also use a natural experiment driving differential increases in the supply of real estate assets across the United States: The Defense Base Closure and Realignment Act of 1990. Consistent with a supply-side view of capital structure, we find that asset redeployability is a main driver of leverage when credit frictions are high.